3-Deoxysappanchalcone Promotes Proliferation of Human Hair Follicle Dermal Papilla Cells and Hair Growth in C57BL/6 Mice by Modulating WNT/β-Catenin and STAT Signaling - Kim, Young Eun (Biomol Ther (Seoul), 2016)
3-Deoxysappanchalcone (3-DSC) has been reported to possess anti-allergic, antiviral, anti-inflammatory and antioxidant activities. In the present study, we investigated the effects of 3-DSC on the proliferation of human hair follicle dermal papilla cells (HDPCs) and mouse hair growth in vivo. A real-time cell analyzer system, luciferase assay, Western blot and real-time polymerase chain reaction (PCR) were employed to measure the biochemical changes occurring in HDPCs in response to 3-DSC treatment. The effect of 3-DSC on hair growth in C57BL/6 mice was also examined. 3-DSC promoted the proliferation of HDPCs, similar to Tofacitinib, an inhibitor of janus-activated kinase (JAK). 3-DSC promoted phosphorylation of β-catenin and transcriptional activation of the T-cell factor. In addition, 3-DSC potentiated interleukin-6 (IL-6)-induced phosphorylation and subsequent transactivation of signal transducer and activator of transcription-3 (STAT3), thereby increasing the expression of cyclin-dependent kinase-4 (Cdk4), fibroblast growth factor (FGF) and vascular endothelial growth factor (VEGF). On the contrary, 3-DSC attenuated STAT6 mRNA expression and IL4-induced STAT6 phosphorylation in HDPCs. Finally, we observed that topical application of 3-DSC promoted the anagen phase of hair growth in C57BL/6 mice. 3-DSC stimulates hair growth possibly by inducing proliferation of follicular dermal papilla cells via modulation of WNT/β-catenin and STAT signaling.